Design protection for WDM optical networks. - Crochat, O. (IEEE Journal on selected areas in communications)
With wavelength division multiplexing (WDM) networks the failure of a single link or component may cause the simultaneous failure of several optical channels, potentially making impossible restoration by rerouting directly in higher layers directly using the optical network (SDH, ATM, internal protocol (IP)). To address this, we introduce the concept of design protection, which aims at making such failure propagations impossible. We present the disjoint alternate path (DAP) algorithm which places optical channels in order to maximize design protection. We show the result on various network examples